The Application of Restorative Justice in Resolving Criminal Acts of Defamation through Social Media (A Study at the Cyber Directorate of the North Sumatra Regional Police) - Chindy Lovica Br Bangun; Rizkan Zulyadi; Serimin Pinem (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This thesis research is entitled The Implementation of Restorative Justice in Resolving Criminal Acts of Defamation Through Social Media (A Study of the Cyber Directorate of the North Sumatra Regional Police). The formulation of the problem is (1) What are the legal rules of restorative justice in legislation? (2) How is the implementation of restorative justice carried out by the North Sumatra Regional Police in resolving criminal acts of defamation through social media? (3) What are the obstacles to the North Sumatra Regional Police in implementing restorative justice to resolve criminal acts of defamation through social media? The research method used is normative juridical legal research, with a descriptive analytical research type. To approach the problem using a normative juridical approach. The data used are primary and secondary data. The results of the study show that (1) The legal basis for restorative justice in legislation, namely Police Regulation No. 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice, Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, Circular Letter of the Chief of Police No. SE/8/VII/2018 of 2018 concerning the Implementation of Restorative Justice in the Settlement of Criminal Cases, Perma No. 1 of 2024 concerning Guidelines for Prosecuting Criminal Cases Based on Restorative Justice. (2) The implementation of restorative justice carried out by the North Sumatra Regional Police in resolving criminal acts of defamation through social media is based on Police Regulation Number 8 of 2021 by bringing together the perpetrator and victim to reconcile and compensate for the losses experienced by the victim. (3) The obstacle for the North Sumatra Regional Police in implementing restorative justice to resolve criminal acts of defamation through social media is that there are still members of the North Sumatra Regional Police who do not understand the process of resolving criminal cases through restorative justice.